Measurement of the ratio of branching fractions B(B+c → B0sπ+)/B(B+c → J/ψπ+) - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Caspary, Rowina; Frau, Giulia; Gerick, David; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; et al. (Journal of high energy physics, 2023)
The ratio of branching fractions of {B}_c^{+}\to {B}_s^0{\pi}^{+} and {B}_c^{+}\to J/\psi {\pi}^{+} decays is measured with proton-proton collision data of a centre-of-mass energy of 13 TeV. The data were collected with the LHCb experiment during 2016-2018, corresponding to an integrated luminosity of 5.4 fb−1. The {B}_s^0 mesons are reconstructed via the decays {B}_s^0\to J/\psi \phi and {B}_s^0\to {D}_s^{-}{\pi}^{+}. The ratio of branching fractions is measured to be \mathcal{B}\left({B}_c^{+}\to {B}_s^0{\pi}^{+}\right)/\mathcal{B}\left({B}_c^{+}\to J/\psi {\pi}^{+}\right)=91\pm 10\pm 8\pm 3 where the first uncertainty is statistical, the second is systematic and the third is due to the knowledge of the branching fractions of the intermediate state decays.